Legal and Moral Aspects of Confidential Cooperation between Individuals and Law Enforcement Agencies - V. M. Davydiuk (Bulletin of Kharkiv National University of Internal Affairs)
The legislative regulation of using confidants in Ukraine, as well as the moral aspects of confidential cooperation between individuals and law enforcement agencies have been analyzed. Some reasons that contributed to the regulation of confidential cooperation at the legislative level have been revealed in the historical retrospective; the correlation of the terms of “assistance” and “cooperation” used in the operative and search legislation has been demonstrated. It has been substantiated that in the course of studying the activities of special forces of operative and search activity it is advisable to use a narrower term of “cooperation”, which reflects the specifics of the activity of such forces. The norms of not secret normative legal acts have been outlined, which enshrined the conceptual bases of work with confidants. The emphasis has been made on the need to regulate not only the rights of the confidants, but also their obligations.